Morphodynamic modeling of aeolian dunes: Review and future plans - Ribeiro Parteli, Eric Josef; Kroy, Klaus; Tsoar, Haim; Andrade, José S.; Pöschel, Thorsten (European Physical Journal - Special Topics, 2014)
Sand dunes are ubiquitous in deserts, on coasts, on the sea bottom, and on the surface of Mars, Venus and Titan. The quantitative understanding of dune dynamics is thus of relevance for a broad range of physical, geological and planetary sciences. A morphodynamic model for dunes, which combines an analytical description of the average turbulent wind field over the topography with a continuum saltation model, has proven successful to quantitatively reproduce the shape of aeolian dunes of different types. We present a short review on the physics of dune formation and the model development, as well as some future plans for further developments and applications.